2008
DOI: 10.4103/1463-1741.40823
|View full text |Cite
|
Sign up to set email alerts
|

Monetary value of undisturbed sleep

Abstract: Sleep undisturbed by noise has a remarkably high monetary value for people, which should be considered in political decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A recent study from Switzerland concluded that one night’s undisturbed sleep was worth CHF 7–24 (approx. 5–15 EUR) depending on severity of disturbance [ 8 ]. In the EU 22, the social cost of road traffic noise is estimated to be at least €38 (30–46) billion per year, which is approximately 0.4% of gross domestic product (GDP) and approximately one third of the social costs for traffic related accidents [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from Switzerland concluded that one night’s undisturbed sleep was worth CHF 7–24 (approx. 5–15 EUR) depending on severity of disturbance [ 8 ]. In the EU 22, the social cost of road traffic noise is estimated to be at least €38 (30–46) billion per year, which is approximately 0.4% of gross domestic product (GDP) and approximately one third of the social costs for traffic related accidents [ 9 ].…”
Section: Introductionmentioning
confidence: 99%